The weakest link?: investigative issues in serial sexual assault that lead to wrongful conviction - Sorochinski, Marina (International journal of law, crime and justice, 2023)
Wrongful conviction of an innocent person is an extreme type of injustice that plagues the criminal justice system today. Wrongful conviction for a sexual offense is especially traumatic for the individual due to the inherent stigma surrounding this type of crime; however, there is a dearth of research focusing on the unique aspects of both the offense and the investigation that may contribute to those convictions. The current study sought to answer the following research questions: 1-Are most sexual assault wrongful convictions in series inter-racial? 2- Does relational misattribution play a role in wrongful conviction for sexual assault? 3-Where in the series do wrongful convictions occur? 4-Do wrongful convictions in serial sexual assault cases occur primarily due to behavioral inconsistency on the part of the perpetrator (i.e., the crime for which there is a wrongful conviction appears to be significantly different from the rest of the series) leading to linkage blindness? 5-To what extent does police misconduct and other investigative issues play a role in mishandling of the offense as a one-off as opposed to part of series? Data for this study included 43 violent sexual series where a proven wrongful conviction was present for at least one of the crimes. Results suggest that thorough investigation, evidence testing, and the ability to reopen cases after similar incidents can reduce wrongful sexual assault convictions. Distinguishing between group and solo offending, stranger and acquaintance offenses, and developing investigative models that account for serial crime behavior change can improve investigative accuracy.